Nursing diagnosis handbook : - Ackley, Betty J. (Mosby, 2006)
This bestselling reference helps users make nursing diagnoses and write care plans with ease and confidence. It helps nurses correlate nursing diagnoses with known information about clients on the basis of assessment findings, established medical or psychiatric diagnoses, and the current treatment plan. This extensively revised and updated edition presents the most up-to-date information on all 2005-2006 NANDA-approved nursing diagnoses. You'll also appreciate the handbook's integration of both the NIC and NOC taxonomies; evidence-based nursing interventions; home care; client/family teaching; and multicultural, geriatric, and pediatric considerations.